Analisis Model Pembelajaran Pendidikan Kristen: Integrasi Wawasan Dunia Kristen Dalam Blended Learning - Asnita Basir Leman (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
Abstract:Learning is feeding the soul. When Jesus gave the great commission to make disciples of all nations, it was complemented by the words and “teach them tērein (to observe, keep, preserve) all that He commanded the disciples.” Difficulties and obstacles in Christian education often occured due to fail in understanding the essence, purpose, content, concepts and context of learning that create chaos in its application. Meanwhile, the rapid growth in the field of educational psychology has caused lessons content and the teaching methods to be strongly influenced by secularism with the philosophy of humanism and relativism. The technological developments were triggered by the unpredictable global Covid-19 pandemic situation in 2020, forcing educators to immediately reformulate learning patterns to be more conducive. This article aims to analyze the blended learning model for Christian education, bya integrating educational psychology theories with the Biblical truth based on concept of christian worldview. The findings and conclusions are expected to contribute to the preparation of Christian education programs, applications and learning modules.Keywords: christian education; christian worldview; cultural mandate; gospel mandate; covid-19 pandemic; blended learning; mete cognitive.  Abstrak:Belajar ialah memberi makanan bagi jiwa. Ketika Yesus memberi amanat agung untuk menjadikan segala bangsa murid-Nya, itu dilengkapi dengan kata dan “ajarlah mereka tērein (memperhatikan, menyimpan, melestarikan) semua yang telah diperintahkan-Nya kepada murid-murid.” Banyak kali kesulitan dan kendala dalam pendidikan kristen terjadi karena kegagalan dalam memahami esensi, tujuan, konten, konsep dan konteks pembelajaran menyebabkan kekacauan dalam penerapannya. Sementara itu pertumbuhan pesat di bidang psikologi pendidikan menyebabkan konten pelajaran dan metode pengajaran sangat dipengaruhi oleh sekularisme dengan filosofi humanisme dan relativisme. Perkembangan teknologi dipicu situasi pandemi covid-19 yang tak terduga secara global tahun 2020, memaksa kalangan pendidik segera melakukan formasi ulang pola pembelajaran yang lebih kondusif. Artikel ini bertujuan menganalisis model pembelajaran blended learning bagi pendidikan kristen, dengan mengintegrasikan teori-teori psikologi pendidikan dengan kebenaran Alkitab berdasarkan konsep wawasan dunia kristen. Temuan dan kesimpulan diharapkan dapat memberi kontribusi bagi penyusunan program, aplikasi dan modul-modul pembelajaran pendidikan kristen ke depan.Kata Kunci: pendidikan Kristen; wawasan dunia Kristen; mandat budaya; mandat penginjilan; pandemi covid-19;blended learning; meta koginitif.